Fuzzy Implementation in The Selection of A Chieving Employees at PT. Sumber Barkah using Matlab Software - Sestri Novia Rizki (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
A company must set a high standard of discipline so that the company can develop quickly. A good company cannot be separated from the performance of employees in the form of standard rules made. With the standard, the company can see employees who excel and can be used as examples for other employees. There are 3 generated criteria such as performance, target and absence. The main purpose of this study is to provide criteria for selecting outstanding employees in a company. This study uses mamdani which uses the lowest min value and uses the AND operator to get the results. There are four things in the Mamdani fuzzy process, the first is the fuzification of the determination of the input value, the second is the application of the implication function, the third is the inference rules and the last is defuzzification. The results of this study can be used as a standard in determining outstanding employees at PT Berkah